Assessing thyroid health: phenotypic age compared to chronological age - Yang, Dongyu; Lu, Cihang; Zhang, Haonan; Shi, Xiaoguang; Sun, Ying; Shao, Ying; Fan, Shuting; Tian, Lijun; Teng, Di (Frontiers in Endocrinology, 2025)
IntroductionAging is associated with thyroid dysfunction, but the role of phenotypic age, a biological aging measure derived from nine clinical biomarkers and chronological age, remains unclear.MethodsThis cross-sectional study included 6,681 adults from the National Health and Nutrition Examination Survey (NHANES, 2007–2012) with complete thyroid function and age data. Participants were grouped into quartiles based on chronological and phenotypic age. Weighted multinomial logistic regression was used to assess the association between aging and thyroid disorders, followed by the use of restricted cubic splines (RCSs) to explore potential nonlinear relationships. Subgroup and sensitivity analyses were conducted to test robustness. Mediation analysis assessed the role of phenotypic age components in the link between phenotypic age and thyroid dysfunction.ResultsThyroid-stimulating hormone (TSH) and free thyroxine (FT4) exhibited U-shaped relationships with both chronological and phenotypic age, while free triiodothyronine (FT3) showed a nonlinear association with chronological age and a negative linear correlation with phenotypic age. The age gap (phenotypic age minus chronological age) was positively associated with TSH and nonlinearly with FT4. Thyroid peroxidase antibody (TPOAb) exhibits a nonlinear association with both age types, and thyroglobulin antibody (TGAb) has a positive linear association with chronological age. PPhenotypic age showed stronger linear associations with TPOAb positivity (PTPOAb), TGAb positivity (PTGAb), overt hyperthyroidism, and subclinical hypothyroidism than chronological age. Overt hypothyroidism demonstrated an inverted U-shaped association with both age metrics and a positive correlation with age gap. Mediation analysis revealed that mean cell volume mediated 10% of the association between phenotypic age and overt hypothyroidism, while lymphocyte percentage exhibited a negative mediation effect (−26%) in the association between phenotypic age and subclinical hypothyroidism.DiscussionPhenotypic age better captures aging-related changes in thyroid function than chronological age and may serve as a useful biological aging marker in clinical endocrine research.